2023
DOI: 10.1093/plphys/kiad063
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics analysis reveals spatiotemporal regulation and function of heteromorphic leaves in Populus

Abstract: Despite the high economic and ecological importance of forests, our knowledge of the adaptive evolution of leaf traits remains very limited. Euphrates poplar (Populus euphratica), which has high tolerance to arid environment, has evolved four heteromorphic leaf forms, including narrow (linear and lanceolate) and broad (ovate and broad-ovate) leaves on different crowns. Here, we revealed the significant functional divergence of four P. euphratica heteromorphic leaves at physiological and cytological levels. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Each type of heteromorphic leaves with different leaf ages was replicated three times for sampling. The napkin was used to delicately clean the leaves, which were then rapidly frozen in liquid nitrogen and stored at an ultra-low temperature of -80℃ in a refrigerator for RNA-seq analysis (the dataset has been made available to the public for access [ 7 ] and preservation through the National Genomics Data Center ( https://ngdc.cncb.ac.cn/ ), under project number PRJCA005959.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each type of heteromorphic leaves with different leaf ages was replicated three times for sampling. The napkin was used to delicately clean the leaves, which were then rapidly frozen in liquid nitrogen and stored at an ultra-low temperature of -80℃ in a refrigerator for RNA-seq analysis (the dataset has been made available to the public for access [ 7 ] and preservation through the National Genomics Data Center ( https://ngdc.cncb.ac.cn/ ), under project number PRJCA005959.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, Populus euphratica characterized by its extraordinary tolerance to drought and salinity, serves as a pivotal species in desert oases and stands out as an exceptional relic plant thriving in extremely arid environments [ 5 , 6 ]. P. euphratica exhibits a distinct pattern of leaf heteroblasty, with adult trees displaying a sequential production of linear (Li, leaf index ≥ 4), lanceolate (La, 2 ≤ leaf index < 4), ovate (Ov, 1 ≤ leaf index < 2), and broad ovate (Bo, leaf index < 1) leaves as they ascend from the lower canopies to the upper canopies, accompanied by a gradual increase in leaf width and area [ 7 ]. Previous research indicated that broad Ov and Bo leaves in P. euphratica exhibit greater resilience to drought than narrow Li and La leaves, as evidenced by their thicker palisade tissue and enhanced photosynthetic activity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each type of heteromorphic leaves with different leaf ages was replicated three times for sampling. The napkin was used to delicately clean the leaves, which were then rapidly frozen in liquid nitrogen and stored at an ultra-low temperature of -80℃ in a refrigerator for RNA-seq analysis (the dataset has been made available to the public for access [34] and preservation through the National Genomics Data Center (NGDC, https://ngdc.cncb.ac.cn/), under project number PRJCA005959).…”
Section: Promoter Analysis Of Gifmentioning
confidence: 99%
“…Many genes related to hormone regulation pathways and environmental stress have been screened out in P. euphratica [ 8 , 9 ], Juniperus flaccida , Pinus cembroides [ 10 ], and some aquatic plants [ 11 ], which are essential in regulating vascular development, stomatal morphology, leaf polarity, and epidermal cell differentiation. Recent studies have employed multi-omics analysis to investigate the regulation and function of heteromorphic leaves [ 12 ]. Nevertheless, the exact mechanism of heteromorphic leaves formation has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%